Computer simulation of airflows generated by jet fans in real road tunnel by parallel version of FDS 6. Issue 1 (2nd January 2021) - Weisenpacher, Peter; Valasek, Lukas
Abstract: In this paper the FDS 6 code ability to simulate the airflows generated by jet fans in a real road tunnel is studied. A transient model of the 898 m long bi-directional highway Polana tunnel is created including details of the tunnel geometry as emergency lay-bys and traffic signs. The absolute roughness of the tunnel walls of 70 mm is determined to represent the influence of curved tunnel geometry and tunnel equipment not explicitly modelled on the tunnel airflows and their retardation. The simulations results are compared against on-site measurements during a full-scale ventilation test conducted in the Polana tunnel in 2017. The comparison includes steady-state bulk airflow velocity and velocity profile investigated by a grid of five anemometers. The simulations results are in good accordance with experimental data with relative errors below 2% for bulk velocities and typically below 9% for velocities measured by particular grid anemometers. Specific circumstances where errors exceed the latter value are discussed. The influence of unknown external dynamic pressure fluctuations on the simulation results is also analysed. Optimal settings for parallel computations are determined from the point of view of simulation accuracy and performance. The model is intended for purposes of tunnel fires modelling.